2022
DOI: 10.1111/irv.13045
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of activities of daily living function in hospitalized patients with nursing and healthcare‐associated pneumonia due to COVID‐19

Abstract: Nursing and healthcare‐associated pneumonia (NHCAP) is associated with decreased physical function. We investigated the functional outcomes at 1 year after hospital discharge in patients with COVID‐19 pneumonia. Functional decline rates for calculating the Barthel Index at the time of hospital discharge and at 1 year after hospital discharge were significantly higher in the NHCAP group than the community‐acquired pneumonia group (at hospital discharge, 54.0% vs. 31.2%, respectively, p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…In countries with an aging population or many older people, physicians should emphasize the function of activities of daily living (ADL) as a prognostic assessment of pneumonia, not just mortality [ 8 ]. Numerous studies have revealed that the diseases of poor functional status, multiple comorbidities, frailness, dysphagia, and malnutrition are highly prevalent in geriatric pneumonia and are related to adverse outcomes [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In countries with an aging population or many older people, physicians should emphasize the function of activities of daily living (ADL) as a prognostic assessment of pneumonia, not just mortality [ 8 ]. Numerous studies have revealed that the diseases of poor functional status, multiple comorbidities, frailness, dysphagia, and malnutrition are highly prevalent in geriatric pneumonia and are related to adverse outcomes [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%